Tobacco smoke as a risk factor for allergic sensitization in adults - Mónico, Beatriz (2020)
Allergic sensitization to aeroallergens is a common phenomenon and a crucial step in the development of allergic diseases. Nonetheless, the influence of tobacco smoke exposure on the development of allergic sensitization in adults is quite complex and not totally understood. [...]